Molecular Characterization and Fungicidal Efficacy Against Rhizoctonia Isolates from Rice and Potato - Mayur R. Thesiya; Ajaysingh Thakur; Vaishali Ladumor; Subash Thapa; Pragya Kumari (The Bioscan, 2024)
This study aimed to characterize Rhizoctonia isolates from rice sheath blight (R-1) and potato (P-1) infections and evaluate the efficacy of diverse fungicides against them. Molecular analysis identified the rice isolate (R-1) as belonging to the AG-1 group, displaying a distinct 265 bp band, while the potato isolate (P-1) exhibited amplification at 500 bp using Rs1F2(F)/Rs2R1(R) markers. Fungicide efficacy testing against R-1 revealed significant inhibition by Bavistin 50 EC, Titan Classic 5 EC, Orius 25 EC, and Emesto Prime 240 ES across various concentrations. Tilt 25 EC and Monceren 250 SC exhibited inhibition at 10 ppm and 100 ppm, while Fujita 40 EC showed the least inhibition (88.4% at 100 ppm). For P-1, Emesto Prime 240 ES and Monceren 250 SC consistently inhibited growth across 5–100 ppm. These findings highlight differential responses of Rhizoctonia isolates to fungicides, identifying potential candidates for effective disease management in rice and potato cultivation. Understanding fungal behavior and fungicide interactions is crucial for sustainable disease control. Further research should explore the mechanisms driving these responses to develop targeted management strategies, ultimately improving crop yield and quality.